New strigolactone analogs as plant hormones with low activities in the rhizosphere - Boyer, François-Didier; de Saint Germain, Alexandre; Pouvreau, Jean-Bernard; Clavé, Guillaume; Pillot, Jean-Paul; Roux, Amélie; Rasmussen, Amanda; Depuydt, Stephen; Lauressergues, Dominique; Frei dit Frey, Nicolas; Heugebaert, Thomas S.S.; Stevens, Christian V.; et al. (Elsevier, 2014)
Strigolactones (SLs) are known not only as plant hormones, but also as rhizosphere signals for establishing symbiotic and parasitic interactions. The design of new specific SL analogs is a challenging goal in understanding the basic plant biology and is also useful to control plant architectures without favoring the development of parasitic plants. Two different molecules (23 (3′-methyl-GR24), 31 (thia-3′-methyl-debranone-like molecule)) already described, and a new one (AR36), for which the synthesis is presented, are biologically compared with the well-known GR24 and the recently identified CISA-1. These different structures emphasize the wide range of parts attached to the D-ring for the bioactivity as a plant hormone. These new compounds possess a common dimethylbutenolide motif but their structure varies in the ABC part of the molecules: 23 has the same ABC part as GR24, while 31 and AR36 carry, respectively, an aromatic ring and an acyclic carbon chain. Detailed information is given for the bioactivity of such derivatives in strigolactone synthesis or in perception mutant plants (pea rms1 and rms4, Arabidopsis max2 and, max4) for different hormonal functions along with their action in the rhizosphere on arbuscular mycorrhizal hyphal growth and parasitic weed germination.